Can neurophysiological assessment improve timing of intervention in posthaemorrhagic ventricular dilatation?. Issue 4 (20th December 2012) - Klebermass-Schrehof, Katrin; Rona, Zsofia; Waldhör, Thomas; Czaba, Christine; Beke, Anna; Weninger, Manfred; Olischar, Monika
Abstract : Objective: Intraventricular haemorrhage is still the most common cause of brain lesion in preterm infants and development of a posthaemorrhagic ventricular dilatation (PHVD) can lead to additional neurological sequelae. Flash visual evoked potentials (fVEP) and amplitude-integrated electroencephalography (aEEG) are non-invasive neurophysiological monitoring tools. The aim of the study was to evaluate fVEPs and aEEGs in preterm infants with progressive PHVD prior to and after neurosurgical intervention for cerebrospinal fluid removal and to correlate the findings with severity of ventricular dilatation. Design: fVEPs and aEEGs were performed weekly in infants with developing PHVD. As soon as the ventricular index reached the 97th percentile recordings were performed twice a week. Methods: 17 patients admitted to the neonatal intensive care unit of the Medical University of Vienna who developed progressive PHVD were evaluated using fVEP and aEEG until and after reduction of intracranial pressure by placement of an external ventricular drainage. Results: In all 17 cases (100%) wave latencies of fVEP increased above normal range and aEEG showed increased suppression in 13 patients (76%) with increasing ventricular dilatation. Both methods showed normalisation of patterns mostly within a week of successful therapeutic intervention (mean 8.5 days). Both changes in fVEP latencies and aEEG background patterns were detected before clinical signs of elevated intracranial pressure occurred. In only 10 patients (58.8%) ventricular width exceeded the 97th percentile+4 mm. Conclusions: fVEP and aEEG are useful additional tools for the evaluation of preterm infants with progressive PHVD.